(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Page load speed reflects the website´s performance. It has a significant influence on user experience and satisfaction. In this work we study and analyze the reasons cause the slowness of webpages laod speed. By the deep invistigation of the related literature and the reviwe of websites’s speed testing services from different perspectives such as functions, interface and additional settings. We present a detailed recommendations that can be followed to optimize site's performance. Our hypotheses about reliability of website speed testing has been tested and conformed experimentally. 378 individual speed tests with various combinations of settings experiemnts have been performed to confirm out hypotheses, and recommendations have been provided based on our results. We believe that following these rules would ensure significantly more reliable website speed testing in comparison with a common practice.